Engaging males to improve nutrition outcomes in young children in Bihar - Thakur, Putul; Akhauri, Santosh; Pradhan, Narottam; Bhanot, Andy; Kumar, Manoj; Kumar, Mani; Singh, Neelmani; Mondal, Sudipta (Frontiers in Nutrition, 2025)
Poor dietary practices among children aged 6–23 months pose a critical public health challenge, hindering their physical and cognitive development. The National Family Health Survey-5 (NFHS-5) reveals that only 11% of children in this age group consume diets meeting the minimum dietary diversity requirements. To address this, a targeted intervention was designed and implemented to improve dietary diversity in children. This study evaluates the intervention’s impact on enhancing dietary diversity and fostering changes in gender norms, such as increased male participation in nutrition-related decision-making, food procurement, shared childcare responsibilities, and discussions about children’s nutritional needs. This research employed a quasi-experimental design with baseline and endline rounds. The intervention and control blocks were selected from the same district based on matching criteria such as population size, literacy rate, etc. The sample size was determined using a two-sample proportion formula to detect an 9% difference between the intervention and control groups, with a 95% confidence level and 80% statistical power. Household listing identified 1,684 and 1,362 children aged 6–11 months in the intervention and control blocks, respectively. 400 fathers and 400 mothers were randomly sampled from both arms in each survey round. The intervention’s impact was assessed using a difference-in-differences (DID) approach. The results revealed significant improvements in the minimum dietary diversity of children aged 6–23 months (DID coefficient, 21%; p < 0.00). At baseline, the intervention and control groups had similar dietary diversity (14% and 13%, respectively), but by endline, the intervention group had significantly improved to 50% compared to 29% in the control group. Knowledge of dietary diversity increased substantially among mothers (DID: 31.3%; p < 0.00) and fathers (DID: 15.6%, p < 0.00). Collaborative meal planning improved (DID: 9.8%; p < 0.00) along with better planning for purchasing vitamin A-rich foods (DID: 28.1%; p < 0.00). These findings highlight the effectiveness of engaging men in nutrition programs to support women in child-feeding practices. The intervention improved dietary practices for young children and promoted a gender-inclusive approach. Scaling this program to other regions could enhance child nutrition outcomes and contribute to better child health and development.